Keragaman parasitoid erionota thrax l. Pada dua Jenis tanaman pisang bermikoriza di kabupaten deli serdang - Setiawan Setiawan; Maimunah Maimunah; Suswati Suswati (Universitas Medan Area, 2019)
The constraints in the cultivation of banana plants is the high number of pests that damage plants in vegetative vases. The study was conducted in the Farmers' Land Group of the United Society of Sampali Village, Percut Sei Tuan District, Deli Serdang Regency in May-July 2019. The research method used was descriptive analysis method using (random sampling). Observation parameters consisted of population density, pest attack rate, egg parasitoids, larva parasitoids, pupa parasitoids, parasitoids identification, species diversity index, species evenness index, and relative abundance. There are 4 types of parasitoids namely Braconidae sp 1 (Hymenoptera: Braconidae), Tachinidae sp 1 (Diptera: Tachinidae), Xanthopimpla gampsura (Hymenoptera: Ichneumonidae) and Brachymeria lasus Walker (Hymenoptera: Chalcididae). Erionota thrax L. parasitoids diversity index was 0.661369 in the low diversity level, and the highest relative abundance of Brachymeria lasus Walker was 86.87%, the attack rate of Erionota thrax on Barangan bananas reached 46%, the level of Erionota thrax on Kepok banana reached 32%.